The Mediation Role of Self-Efficacy on Innovative Work Behavior - Izza, Ainul; Indarto, Indarto; Albert, Albert (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine the effect of Organizational Innovation and Perception of Organizational Support on Innovative Work Behavior through Self-Efficacy. The research sample consisted of 108 State Civil Apparatus in the Regional Secretariat of Grobogan Regency, using a quantitative approach with data analysis using SmartPLS v.3. The results of the study indicate that Organizational Innovation and Perception of Organizational Support have a positive effect on self-efficacy. In addition, Organizational Innovation and Perception of Organizational Support also have a positive effect on innovative work behavior, both directly and through self-efficacy. Self-efficacy was found to have a positive effect on innovative work behavior. Thus, self-efficacy acts as an intervening variable in the influence of Organizational Innovation and Perception of Organizational Support on Innovative Work Behavior.